(2x)³+(3y)³ using (a+b ) ( a²-ab+b²)
Answers
Answered by
0
Answer:
(2x+3y)(4x²-6xy+9y²)
Step-by-step explanation:
(2x)³+(3y)³ compare with a³+b³;
a = 2x
b = 3y
Substituting,
(a+b)(a²-ab+b²) = (2x+3y)(4x²-6xy+9y²)
Answered by
0
Answer:
Step-by-step explanation:
(2x)^3+(3y)^3
= (2x+3y){(2x)^2-2x.3y+(3y)^3}
=(2x+3y){4x^2-6xy+9y^2}
=(2x+3y){4x^2-(3+3)xy+9y^2}
= (2x+3y){4x^2-3xy+3xy+9y^2}
= (2x+3y){x(4x-3y)+3y(x+3y)}
Similar questions
Math,
1 month ago
English,
1 month ago
Biology,
3 months ago
Math,
11 months ago
India Languages,
11 months ago